Content of the National Code in Popular Tales at the Budjak: Array - Radkina, Valentina (Journal of Danubian Studies and Research, 2020)
The article considers a folk tale as a means of preserving national identity, expressed in the national code – a peculiar system of signs that expresses the specifics of the national culture of a certain ethnic group. Analyzing Romanian (Moldavian), Russian, Bulgarian and Ukrainian fairy tales preserved in Bessarabia, the author comes to the conclusion that there is a regional code that preserves the common features of national communities living in this territory.